The molecular cloning and expression of the African horsesickness VP7 viral gene in the yeast Saccharomyces cerevisiae - Stevens, Liesel (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1997.